Potential non-phytopathogenic filamentous fungi for bioconversion of domestic wastewater sludge - Molla , Abul Hossain; Fakhru’l-Razi, Ahmadun; Hanafi, Mohamed Musa; Abd-Aziz, Suraini; Alam, Md. Zahangir (Taylor and Francis Inc., 2002)
Ten filamentous fungi adapted to domestic wastewater sludge (DWS)were further studied to evaluate their potential in terms of adaptation to higher sludge supplemented growing media and phytopathogenicity (induction of diseases to plants) to three germinating crop (Corn: Zea mays, Mung bean: Phaseolus aureus and Mustard: Brassica napus) seeds. The performances of the fungi in seed germination were evaluated based on percent germination index (GI) and infected/spotted seeds on direct fungal biomass (FBM) and fungal metabolite (FM). Significantly the highest biomass production was achieved with RW-Pl 512 and Penicillium corylophilum (WW-P1003) at the highest (25%) sludge supplemented growing media that implied its excellent potentiality of adaptation and multiplication to domestic wastewater sludge. Significantly encouraging results of percent GI and spotted/infected seedlings were observed in FM than FBM by all fungi except the strain Aspergillus niger. A. niger gave the poorest percent of GI (24.30, 26.98 and 00.00%) and the highest percent of infected/spotted seeds (70, 100,and 100%) using FBM for corn, mung bean and mustard, respectively. On the other hand, comparatively the highest percent of GI (107.99,106.25 and 117.67%) and the lowest percent of spotted/infected seedlings (3.3, 3.3 and 3.3%) were achieved with the isolate RW-Pl 512 using FM.In FBM, the superior results of percent GI (86.61, 95.92 and 83.87%) and spotted/infected seedlings (3.3, 63.3 and 43.3%) were obtained by A. versicolor. Several crop seeds were responded differently for different fungal treatments. Hundred percent infected/spotted seeds in FM were recorded only for mustard with Trichoderma family that implied its strong sensitiveness to its metabolites.